Seed priming and foliar application of Moringa oleifera leaf nano-extract enhance growth and chlorophyll in canola (Brassica napus) (Asian Journal of Agriculture, 2025)
Abstract. Dhahir SN, Shaheen MASA. 2025. Seed priming and foliar application of Moringa oleifera leaf nano-extract enhance growth and chlorophyll in canola (Brassica napus). Asian J Agric 9: 433-441. Improving seed germination and physiological traits in crops like canola (Brassica napus) is crucial for enhancing yield and stress tolerance. Nanotechnology, particularly plant-based nano-extracts, offers eco-friendly alternatives for sustainable agriculture. This study evaluated the effects of seed priming and foliar spraying with varying concentrations of Moringa oleifera leaf nano-extract on germination and physiological performance of canola. A greenhouse experiment was conducted using a completely randomized design (CRD) with three nano-extract concentrations (5%, 10%, and 20%) and a distilled water control. The extract, synthesized via silver nitrate, was characterized by UV-Vis spectroscopy (peak at 435 nm), XRD, and SEM, confirming spherical nanoparticles (29-42 nm). Germination and physiological parameters were analyzed using ANOVA (p
Keywords: Canola physiology, foliar spray, Moringa oleifera, seed priming, silver nanoparticles